1990
DOI: 10.1002/mus.880131010
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological spectrum of inclusion body myositis

Abstract: We present electrodiagnostic data on 30 patients with inclusion body myositis (IBM) in order to better delineate its electrophysiological features. Comprehensive electromyography (EMG) and nerve conduction studies (NCS) were performed in all cases. Twelve patients had single fiber electromyography (SFEMG). EMG showed abundant short-small motor unit potentials (MUP) with fibrillations and positive sharp waves in 56.6% of patients, and a mixed pattern of large and small MUP in 36.7%. In 6.7%, only "neurogenic" f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 19 publications
3
29
1
4
Order By: Relevance
“…The semiquantitative assessment used in this study allows easy comparison with routine daily practice in which semiquantitative techniques are most frequently used. The present study confirms several findings reported previously on EMG abnormalities in myositis [10, 11,16,17,18,19,20,21]. Several conclusions can be drawn that add to the present knowledge on EMG in myositis, keeping the retrospective nature of the study in mind.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The semiquantitative assessment used in this study allows easy comparison with routine daily practice in which semiquantitative techniques are most frequently used. The present study confirms several findings reported previously on EMG abnormalities in myositis [10, 11,16,17,18,19,20,21]. Several conclusions can be drawn that add to the present knowledge on EMG in myositis, keeping the retrospective nature of the study in mind.…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that a pattern of long- and short-duration MUPs is typical for IBM [11]. We found this pattern in a majority of patients with IBM and in a large group of patients with DM/PM.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…La afección del sensorio se examina clínicamente y con estudios electrofisiológicos y de neuroconducción, que evidencian la neuropatía axonal sensorial e incremento de la actividad polifásica motora (36,37). Los estudios de laboratorios pueden mostrar elevación de la CK sérica la cual puede estar normal o elevada hasta diez veces (38,39); los anticuerpos antinucleares pueden estar presentes en un 20% de los casos, pero usualmente están ausentes y un 20% de los pacientes pueden tener una gamapatía monoclonal indeterminada. La resonancia magnética puede mostrar afectación muscular focal, atrofia y definir los patrones de pérdida de unidades motoras después del traumatismo de nervios periféricos, por cual es importante para el diagnóstico clínico y seguimiento de respuesta al tratamiento (40)(41)(42)(43).…”
Section: Otros Desórdenes (Raros)unclassified
“…One study reported an increased mean jitter of 83 s compared with an abnormality threshold of 60 s in all of seven IBM patients. 3 Another study reported abnormal jitter in 7 of 12 patients, 4 and a third reported increased jitter or blocking in 5 of 17 patients. 2 Jitter by itself does not cause muscle weakness, but impulse blocking does.…”
mentioning
confidence: 98%